Childhood pneumonia diagnostics: community health workers' and national stakeholders' differing perspectives of new and existing aids. Issue 1 (1st January 2017) - Spence, Hollie; Baker, Kevin; Wharton-Smith, Alexandra; Mucunguzi, Akasiima; Matata, Lena; Habte, Tedila; Nanyumba, Diana; Sebsibe, Anteneh; Thany, Thol; Källander, Karin
ABSTRACT: Background: Pneumonia heavily contributes to global under-five mortality. Many countries use community case management to detect and treat childhood pneumonia. Community health workers (CHWs) have limited tools to help them assess signs of pneumonia. New respiratory rate (RR) counting devices and pulse oximeters are being considered for this purpose. Objective: To explore perspectives of CHWs and national stakeholders regarding the potential usability and scalability of seven devices to aid community assessment of pneumonia signs. Design: Pile sorting was conducted to rate the usability and scalability of 7 different RR counting aids and pulse oximeters amongst 16 groups of participants. Following each pile-sorting session, a focus group discussion (FGD) explored participants' sorting rationale. Purposive sampling was used to select CHWs and national stakeholders with experience in childhood pneumonia and integrated community case management (iCCM) in Cambodia, Ethiopia, Uganda and South Sudan. Pile-sorting data were aggregated for countries and participant groups. FGDs were audio recorded and transcribed verbatim. Translated FGDs transcripts were coded in NVivo 10 and analysed using thematic content analysis. Comparative analysis was performed between countries and groups to identify thematic patterns. Results: CHWs and national stakeholders across the four countries perceived the acute respiratory infection (ARI) timer and fingertip pulse oximeter as highly scalable and easy for CHWs to use. National stakeholders were less receptive to new technologies. CHWs placed greater priority on device acceptability to caregivers and children. Both groups felt that heavy reliance on electricity reduced potential scalability and usability in rural areas. Device simplicity, affordability and sustainability were universally valued. Conclusions: CHWs and national stakeholders prioritise different device characteristics according to their specific focus of work. The views of all relevant stakeholders, including health workers, policy makers, children and parents, should be considered in future policy decisions, research and development regarding suitable pneumonia diagnostic aids for community use.